The crystal structure of (E)-(2-(2-hydroxy-3-methoxybenzylidene)aminophenyl)arsonic acid, C14H14AsNO5 - Cai Bin; Ke Jia-Bo; Wu Cen-Cen; An Yi-Bo; Qiao Yu; Li Shuo (Zeitschrift für Kristallographie - New Crystal Structures)
C14H14AsNO5, monoclinic, P21 (no. 4), a = 8.5830(5) Å, b = 7.0799(5) Å, c = 11.6011(7) Å, β = 100.059(2)∘, V = 694.13(8) Å3, Z = 2, R gt(F) = 0.0288, wR ref(F 2) = 0.0603, T = 150.0 K.